The action of acetyl-L-carnitine in dopaminergic neurotransmission - Cunha, Lídia (2014)
Acetyl-L-Carnitine (ALC) has been described as playing a neuroprotective effect against a variety of substances. However, the molecular mechanisms underlying its action, particularly regarding the induction of changes in neurotransmitter system, are still not fully understood. Using both a cell line and an animal model of exposure to methamphetamine (METH), we aim to contribute to clarify the mechanism by which the administration of ALC alters neurotransmitter release.